IN VITRO ANTIOXIDANT AND PHYTOCHEMICAL ANALYSIS OF DIFFERENT PARTS OF SIMANA LAGI APPLE ([MALUS DOMESTICA BORKH.] SIMANA LAGIâ€) GROWN IN EAST JAVA-INDONESIA - Fidrianny, Irda; Fitrani, Dhella; Kusmardiyani, Siti; Rizaldy, Defri; Ruslan, Komar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objectives: The goals of this research were to observe antioxidant properties from different parts of Simana lagi apple ([Malus domestica Borkh.] Simana lagiâ€) using two antioxidant testing methods which were 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzthiazoline-6- sulfonic acid (ABTS) and correlation of total phenolic and flavonoid content with their inhibitory concentration 50 (IC50) of DPPH and IC50 of ABTS. Methods: Each sample was extracted by reflux using different polarity solvents. The extracts were evaporated using rotary evaporator. Antioxidant activities were tested using DPPH and ABTS assays, determination of total phenolic, and flavonoid content were carried out by ultraviolet-visible spectrophotometry and correlation with their IC50 of DPPH and IC50 of ABTS activities were analyzed by Pearson's method. Results: The ethanolic leaves extract (LV3) of Simana lagi apple also exposed the highest total phenolic content (TPC) (13.88 g gallic acid equivalents/100 g), while the highest total flavonoid content was presented by ethyl acetate extract (LV2) (7.21 g QE/100 g). The lowest IC50 of DPPH scavenging activity 0.19 Î¼g/ml, and the lowest IC50 of ABTS scavenging activity 0.15 Î¼g/ml was given by ethanolic flesh extract (FL3) of Simana lagi apple. There were significantly negative correlation between TPC in all different parts extracts of Simana lagi apple with their IC50 of DPPH and IC50 of ABTS. Conclusions: All different parts extracts of Simana lagi apple were categorized as very strong antioxidant by DPPH and ABTS method (except n-hexane peels extract and n-hexane LV by DPPH method, and n-hexane FE by ABTS method). The major contributor in antioxidant activities of peels, flesh and leaves extracts of Simana lagi apple by DPPH and ABTS methods were phenolic compounds. Antioxidant activities of peels, flesh and leaves extracts of Simana lagi apple showed linear results by DPPH and ABTS methods.